The Role of PPKn Teachers as Evaluators in Improving Student Learning Discipline - Riska Amanda Putra (International Journal of Students Education, 2024)
This research aims to determine the role of PPKn teachers as evaluators in improving student learning discipline. This research uses the Literature review method where the data taken is data excerpts from several articles and journals accessed from Google. Research Results on the role of PPKn teachers as evaluators in improving learning discipline students, Pancasila and Citizenship Education (PPKn) teachers as evaluators carry out continuous learning evaluations to see student success in learning and can improve student learning discipline if the results of student learning evaluations have not shown success. Teachers can carry out their role well when teaching and strengthen and improve students’ compliance with regulations regarding discipline at school. Teachers are expected to always pay attention to students’ disciplinary behavior, especially during learning activities in the classroom. Students are expected to further improve their disciplinary behavior in obeying the rules at school or in the classroom when studying.